Impact of Agricultural Land Use on Nitrate Levels in Lake Manatee, Florida - Craig D. Stanely; R. A. Clarke; Brian L. McNeal; B. W. Macleod (EDIS)
Nutrient enrichment of surface water bodies is often attributed to nonpoint source pollution from agricultural production areas where applied fertilizer has been leached from the point of application. Where this enrichment results in eutrophication of the water body, environmental and/or economic burdens are placed on society to live with or rectify the situation. This is document SL 209, a publication of the Soil and Water Science Department, Florida Cooperative Extension Service, IFAS, University of Florida. Published September 2003.